Sarcoma – correlation between CD73 and PD-L1 and their relationship with prognosis - Abdullah Evren Yetişir; Semra Paydaş; Gülfiliz Gönlüşen; Kıvılcım Eren Erdoğan; Mahmut Büyükşimşek; Ali Oğul; Mert Tohumcuoğlu; Cem Mirili; Ayşegül Yetişir (Polish Journal of Pathology, 2023)
This study aimed to evaluate CD73 and PD-L1 and determine their relationship with each other and with overall survival (OS) in sarcoma patients. The paraffin blocks of 101 patients were analysed. 56.4% were female, and the mean age was 51.39 years. The mean OS was 20.73 months, and the Ki-67 proliferative index was 41.45. A positive correlation was found between CD73 tumour and CD73 tumour-infiltrating lymphocyte (TIL) findings. CD73 tumour and TIL findings were also positively correlated with PD-L1 percentages and PD-L1 intensity. An inverse correlation was detected between OS and CD73 tumour and TIL groups of 5–25%, 25–50%, 50–75%, 75–90%, and > 90%, but no such correlation was found for the ≤ 5% group. There was an inverse correlation between OS and the PD-L1 percentages of  50% and the PD-L1 intensity of weak-moderate and strong, but no correlation was found for the negative values. Lastly, an inverse correlation was found between OS and the Ki-67 proliferative index. We found CD73 and PD-L1 positivity to be associated with decreased OS in sarcoma patients and determined a significant correlation between these parameters. This result is promising in terms of achieving better survival and disease control with anti-CD73 and anti-PD-L1 therapy in selected patients.